In valle lacrymarum: da miséria histérica à infelicidade comum: o percurso de um caso psicanalítico - Trevisan, Neusa Cristina (2019)
The purpose of this study was to demonstrate, through the report of a clinical case, some movements that occurred along a path that led the patient to a change of position in the face of her suffering, concomitantly delineating the exercise of psychoanalysis in this transfiguration. Some considerations are also presented on the psychoanalyst's performance, understanding that when discussing a clinical case, a work of construction between the professional and the patient is revealed. Psychoanalytic concepts such as transference and the subject supposed to know are approached. Certain aspects of hysteria and its history are raised for a better understanding of the case